Query-Biased Web Page Summarisation: A Task-Oriented Evaluation - White, Ryen W.; Jose, Joemon M.; Ruthven, Ian (24th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2001), New Orleans, U.S.A., 2003)
We present a system that offers a new way of assessing web document relevance and new approach to the web-based evaluation of such a system. Provisionally named WebDoc-Sum, the system is a query-biased web page summarizer that aims to provide an alternative to the short, irrelevant abstracts typical of many web search result lists. Based on an initial evaluation the system appears to be more useful in helping users gauge document relevance than the traditional ranked titles/abstracts approach.